Analisis Kepuasan Terhadap Fasilitas Sarana dan Prasarana Olahraga Mahasiswa Institut Teknologi Del - Ezra Dosma Lamtiur Siregar; Mariana Simanjuntak (Jurnal Mahasiswa Kreatif, 2024)
This study aims to analyze the level of student satisfaction with sports facilities and infrastructure at the Del Institute of Technology. Data analysis was carried out using the Structural Equation Model (SEM) through SmartPLS 4.0 and SPSS 25.0 software to test validity and reliability. The results of the study show that the quality of sports facilities at IT Del has a significant influence on student satisfaction. Some of the obstacles found include limitations in the type of facilities, poor condition of facilities, and limitations in staff and coaches. These findings provide input for the campus to improve the quality of sports facilities to increase student satisfaction.